Multi-sensor fusion for autonomous vertical docking in kilometer-scale deep-sea environments - Suohang Zhang; Lin Yu; Shipang Qian; Jiaxuan Song; Ziyang Wan; Ruiheng Liu; Lu Wang; Xinyu Fei; Canjun Yang; Yanhu Chen (Ocean Engineering, 2026)

VVFGO: a robust IMU/AHRS/USBL integrated navigation framework with adaptive virtual velocity factor correction for deep-sea docking - Ruiheng Liu; Xinyu Fei; Suohang Zhang; Yurui Zhang; Shipang Qian; Lu Wang; Yanhu Chen; Canjun Yang (Ocean Engineering, 2026)

Neural Network-Enhanced Robust Navigation for Vertical Docking of an Autonomous Underwater Shuttle Under USBL Outages - Xiaoyan Zhao; Canjun Yang; Yanhu Chen (Journal of Marine Science and Engineering, 2026)
Vertical docking of the autonomous underwater shuttle (AUS) for deep-sea data relay relies heavily on ultra-short baseline (USBL) acoustic positioning, whose measurements can be intermittently unavailable and contaminated by outliers in complex underwater environments. This paper proposes a neural network-enhanced robust navigation framework to improve AUS navigation reliability during acoustically guided vertical docking under USBL outages. First, a model-aided batch maximum a posteriori trajectory estimation method (MA-BMAP) is developed to generate learning quality supervision under sensor-limited conditions. Based on the estimated trajectories, a long short-term memory (LSTM)-based horizontal velocity predictor is integrated into a robust fusion filter with online ocean current estimation, enabling stable state estimation during USBL outages and robust rejection of abnormal USBL measurements. The proposed framework is validated through simulations and field trials in lake and sea environments. In sea trials, during two representative 200 s USBL outage intervals, the end-of-window horizontal position errors are 7.86 m and 4.14 m, respectively, corresponding to AUS-to-docking station distances of 244 m and 51 m. In addition, the introduced USBL outliers are successfully detected and rejected. The results indicate that the proposed method enables accurate and stable navigation during USBL unavailability and rapid recovery once USBL measurements resume, demonstrating its practicality for vertical docking missions.

A Physics-Guided Hybrid Network for Robust Hydrodynamic Parameter Identification of UUVs Under Lumped Disturbances - Xinyu Fei; Lu Wang; Ruiheng Liu; Shipang Qian; Jiaxuan Song; Suohang Zhang; Yanhu Chen; Canjun Yang (Journal of Marine Science and Engineering, 2026)
Accurate identification of hydrodynamic parameters is essential for high-fidelity modeling and control of unmanned underwater vehicles (UUVs). Compared with towing tank experiments and computational fluid dynamics simulations, system identification based on free-running trial data offers a cost-effective and scalable alternative. However, in real ocean environments, unmodeled lumped disturbances—such as shear currents, stratification-induced buoyancy variations, and wave-induced drift forces—strongly couple with the vehicle’s intrinsic dynamics. Conventional least-squares estimators and physics-informed neural networks tend to absorb environmental effects into the physical parameters, leading to physically inconsistent estimates. To address this challenge, this paper proposes a physics-guided hybrid network (PG-HyNet) with input-domain structural decoupling. The architecture explicitly separates the intrinsic rigid-body dynamics from spatially varying environmental disturbances by assigning dynamics-related states to a physics-constrained branch and position-dependent variables to a residual disturbance branch. A staged training strategy is introduced to stabilize identification and suppress parameter drift during optimization. The framework is validated using high-fidelity simulations incorporating shear currents, density stratification, and wave drift effects, as well as real-world lake trial data. The results demonstrate that PG-HyNet significantly improves robustness against disturbance-induced parameter compensation, enabling physically consistent hydrodynamic parameter recovery while accurately capturing spatially varying environmental disturbance effects.

Small-sized fixed domain monitoring underwater profiler: A multi-factor comparative analysis - Yang Zhang; Xin Zhang; Qingchao Xia; Canjun Yang; Ruiyin Song; Dingze Wu; Rui Zhou; Jiayu Hou; Gul Muhammad (Ocean Engineering, 2025)

Towards autonomous sampling of the seafloor hydrothermal plume based on machine vision and real-time temperature detection - Shijun Wu; Xiaofeng Jiang; Xun Wang; Qingchao Xia; Canjun Yang (Ocean Engineering, 2025)

A vertical docking system based on the autonomous underwater shuttle for seafloor communication relay - Xiaoyan Zhao; Xinyu Fei; Suohang Zhang; Ning Tan; Zhangpeng Tu; Anzhe Yi; Yurui Zhang; Canjun Yang; Yanhu Chen (Ocean Engineering, 2025)

Research on the dynamical behavior of air-dropped underwater profiler and virtual mooring strategy for variable pitch angle - Dingze Wu; Rui Zhou; Qingchao Xia; Puzhe Zhou; Xin Zhang; Zhilan Jin; Yang Zhang; Canjun Yang (Ocean Engineering, 2025)

Research on the pitch angle attitude control of underwater vehicles based on a novel butterfly-shaped blocks structure - Yanhu Chen; Xinyu Fei; Xiutong Mu; Xiaoyan Zhao; Suohang Zhang; Canjun Yang (Ocean Engineering, 2024)

Frequency optimization of the AUV wireless charging system for minimum energy dissipation - Ri Lin; Mingwei Lin; Canjun Yang; Dejun Li; Zhuoyu Zhang (Ocean Engineering, 2024)

A review of deep-seawater samplers: Principles, applications, performance, and trends - Shijun Wu; Zhiheng Chen; Shuo Wang; Jian Zhang; Canjun Yang (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Static Model of the Underwater Soft Bending Actuator Based on the Elliptic Integral Function - Ri Lin; Anzhe Yi; Mingwei Lin; Canjun Yang; Zhuoyu Zhang (Journal of Marine Science and Engineering, 2024)
Underwater soft manipulators are increasingly used for grasping underwater organisms and cultural relics due to their compliance and ability to protect delicate objects. Unlike rigid manipulators, these soft manipulators feature underwater soft bending actuators that deform under external forces, making their shape and output force challenging to predict. Consequently, classical beam theory is no longer applicable. To address these issues, this article models the underwater soft bending actuator as a cantilever beam and establishes its shape and output force using elliptic integral functions. Additionally, this article proposes a method for determining the unknown parameters of the driver shape and output force model using optimization techniques and introduces a solution process based on the particle swarm optimization framework. Given the role of tensile and bending stiffness in the actuator’s performance, this paper employs a parameter identification method based on length and bending angle information. Tests demonstrate that the proposed method effectively estimates the deformation and output force of the underwater soft bending actuators, confirming its accuracy.

Underwater fluid-driven soft dock for dynamic recovery of AUVs with improved pose tolerance - Mingwei Lin; Anzhe Yi; Ri Lin; Xin Wu; Bohao He; Bolun Zhang; Canjun Yang (Ocean Engineering, 2024)

A synchronous multi-agent reinforcement learning framework for UVMS grasping - Yanhu Chen; Zhangpeng Tu; Suohang Zhang; Jifei Zhou; Canjun Yang (Ocean Engineering, 2024)

Dual-Mode Square Root Cubature Kalman Filter for Miniaturized Underwater Profiler Dead Reckoning - Yang Zhang; Qingchao Xia; Canjun Yang; Ruiyin Song; Dingze Wu; Xin Zhang; Rui Zhou; Shuyang Ma (Journal of Marine Science and Engineering, 2024)
Miniaturized underwater profilers have the advantages of small size, low cost, and flexible deployment, which play together an important role in the persistent monitoring of a designated ocean area. Based on the demand for ocean observation, the system design, dynamic modeling, and dead reckoning algorithm of a miniaturized underwater profiler are carried out. The process of the persistent monitoring of designated area with a miniaturized underwater profiler is analyzed, and the overall structure of the miniaturized underwater profiler was designed. Additionally, the kinematic and dynamic model of the miniaturized underwater profiler is given based on the inertial and body coordinate systems. Then, according to the state equation and the observation equation of the miniaturized underwater profiler, a dual-mode square root cubature Kalman filter (DSRCKF) algorithm, combining standard SRCKF and adaptive SRCKF, is proposed for the dead reckoning of the miniaturized underwater profiler. Finally, a comprehensive comparison of EKF, UKF, CKF, SRCKF, and DSRCKF and the associated simulations and experiments are conducted to verify the performance of the underwater dead reckoning algorithm for the miniaturized underwater profiler. The results show that the DSRCKF algorithm has a certain role in the dead reckoning of the miniaturized underwater profiler, particularly in the z direction and attitude. In future, a real underwater dead reckoning test using miniaturized underwater profiler will be carried out.

Disposable portable buoy for data transmission between seafloor equipment and onshore laboratories - Yongchao Sun; Shijun Wu; Yanhu Chen; Zhangpeng Tu; Anzhe Yi; Canjun Yang (Ocean Engineering, 2024)

Biofouling recognition and boundary tracking control for underwater cleaning robots - Hang Su; Siyue Liu; Luning Zhang; Yanhu Chen; Canjun Yang (Ocean Engineering, 2024)

Review of underwater adsorptive-operating robots: Design and application - Canjun Yang; Siyue Liu; Hang Su; Luning Zhang; Qingchao Xia; Yanhu Chen (Ocean Engineering, 2024)

Multiphysics Co-Simulation and Experimental Study of Deep-Sea Hydrothermal Energy Generation System - Keren Xie; Tiefeng Li; Yanyan Zhang; Shijun Wu; Canjun Yang (Journal of Marine Science and Engineering, 2023)
With the continuous deepening of research on seafloor hydrothermal observations, the demand for a sustainable power supply of observation equipment is increasingly urgent. A kind of device that utilizes the temperature difference near hydrothermal vents to provide power is studied. However, the frequent experiments required for in-depth research on this device contradict the rare opportunities for hydrothermal field experiments and the difficulty in laboratory replication. In response to the above difficulties, a multiphysics co-simulation of the deep-sea hydrothermal energy generation system is studied in this paper. Firstly, the output performance analysis and modeling of the TEG installed in the device under pressure are carried out. An enhanced heat transfer model of the system is proposed for the hydrothermal fluids in the flow channel of the device. Then, the thermoelectric model of TEG and the heat transfer model of the device are jointly simulated by using Fluent and Simulink software. Eventually, the simulation data are compared with the data obtained through experiments. The average absolute of the relative error of the open-circuit voltage is 5.07%, and the maximum one is 6.28%. The corresponding values of the maximum output power are 5.16% and 6.79%, respectively. Therefore, the performance of the hydrothermal thermoelectric power generation system and the correctness of the proposed overall co-simulation model are verified.

Research on flexible collapsible fluid-driven bionic robotic fish - Qingchao Xia; Hong Li; Nan Song; Zeliang Wu; Xiang Wang; Xu Sun; Sheng Zhang; Canjun Yang (Ocean Engineering, 2023)

Real-time detection of deep-sea hydrothermal plume based on machine vision and deep learning - Xun Wang; Yanpeng Cao; Shijun Wu; Canjun Yang (Frontiers in Marine Science, 2023)
Recent years have witnessed an increase in applications of artificial intelligence (AI) in the detection of oceanic features with the tremendous success of deep learning. Given the unique biological ecosystems and mineral-rich deposits, the exploration of hydrothermal fields is both scientifically and commercially important. To achieve autonomous and intelligent sampling of the hydrothermal plume by using AUV, this paper proposes an innovative method for real-time plume detection based on the YOLOv5n deep learning algorithm designed with a light-weight neural network architecture to meet the requirements of embedded platforms. Ground truth labeler app LabelImg was used to generate the ground truth data from the plume dataset created by ourselves. To accurately and efficiently detect hydrothermal plumes using an embedded system, we improved the original structure of YOLOv5n in two aspects. First, SiLU activation functions in the model were replaced by ReLU activations at shallow layers and Hard-SiLU activations at deep layers to reduce the number of calculations. Second, an attention module termed Coordinate Attention (CA) was integrated into the model to improve its sensitivity to both channel and spatial features. In addition, a transfer learning training method was adopted to further improve the model’s accuracy and generalizability. Finally, we successfully deployed the proposed model in a low-cost embedded device (NVIDIA Jetson TX2 NX) by using the TensorRT inference engine. We then installed the Jetson TX2 NX into a hovering-type AUV as its vision processing unit and conducted a plume detection test in the water tank. The water tank experimental results demonstrated that the proposed method can achieve real-time onboard hydrothermal plume detection.

Research on non-contact wet mateable connector for optical communication and power transmission - Zhiyong Duan; Yurui Zhang; Jiaqi Hu; Bohao He; Canjun Yang (Frontiers in Marine Science, 2023)
At present, contact watertight connectors are commonly utilized for the connection between underwater electromechanical equipment and the seabed observation network. Such traditional watertight connectors are easy to be irreversibly worn when plugging and unplugging, however, they have complicated sealing structures and limited service life. This paper designs a Non-contact Wet Mateable connector for Optical Communication and Power Transmission (OCPT-NWMC), which is based on technology of Contactless Power Transmission (CLPT) and optical communication. Docking structure of the sockets and plugs are designed, facilitating Remotely Operated Vehicle (ROV) to operate. A prototype of the OCPT-NWMC was established. The experimental results show that the connector designed can achieve 200W power transmission, with a maximum power transmission efficiency of 94%. The communication bandwidth reaches 18MHz. The OCPT-NWMC can assist the rapid and safe deployment and operation of seabed observation network.

Performance study of energy conversion system for ocean thermal profiler - Yanhu Chen; Bingzhe Chen; Meiling He; Luning Zhang; Qingchao Xia; Canjun Yang (Frontiers in Marine Science, 2022)
With the increasing scarcity of energy in the world, energy has become an important part of restricting the development and application of traditional ocean profilers. The method of converting ocean thermal energy (OTE) into electrical energy through an energy conversion system is a solution. The model establishment and performance analysis of the energy conversion system are the basis of the ocean thermal profiler (OTP) design. The model and performance are affected by the coupling of multiple parameters, especially rotational speed and pressure. In this study, a universal parameterized model for multi-parameter coupling was proposed. System performance analysis based on experiments including load current, speed, mechanical efficiency and total efficiency was presented. After model parameter identification, the error of mechanical efficiency was within 5%; the total efficiency error was less than 12.8%, and the maximum efficiency point error didn’t exceed 2.21%. The results indicated that the parameterized model was satisfactory for the engineering applications and could guide the design of OTP.

Underwater Electromagnetic Guidance Based on the Magnetic Dipole Model Applied in AUV Terminal Docking - Ri Lin; Yucheng Zhao; Dejun Li; Mingwei Lin; Canjun Yang (Journal of Marine Science and Engineering, 2022)
To address the poor effect of optical/visual guidance used in AUV terminal docking with strong background light and turbid water quality, an underwater electromagnetic guidance method based on the magnetic dipole model is proposed in this paper. According to the magnetic dipole model, the electromagnetic field of 1 kHz frequency generated by the coil in the range of terminal docking is the near field, where the position can be figured out through the amplitude and phase information of three orthogonal magnetic field intensity vectors. A triaxial-coil magnetometer with three orthogonal coils and a method for extracting the amplitude and phase information of the induced voltage are presented in this paper. According to Faraday’s law, the amplitude and phase information of the induced voltage of a triaxial-coil magnetometer replace the information of magnetic field intensity in relation to positioning. The underwater positioning results show that the average positioning error within 6 m can reach the centimeter level. Five underwater terminal docking tasks were carried out, and four of them were successfully completed, which verified the feasibility of the proposed method.

Research on the Depth Control Strategy of an Underwater Profiler Driven by a Mixture of Ocean Thermal Energy and Electric Energy - Qingchao Xia; Bingzhe Chen; Xiaotong Sun; Canjun Yang; Sheng Zhang; Yanhu Chen (Journal of Marine Science and Engineering, 2022)
Marine resources are rich and contain an enormous amount of energy. The exploration of marine resources and the effective use of ocean energy have gradually become the research focus of scholars all over the world. A profiler driven by ocean thermal energy can monitor the vertical profile of the surrounding sea area for a long time. To realize the levitation at a fixed water depth on the premise of saving energy, in this paper, a new buoyancy regulation system driven by the mixture of ocean thermal energy and electric energy is designed, and a new depth control strategy for the hybrid drive is proposed. Compared with the traditional profiler, the new profiler, in which the main energy required for buoyancy regulation is provided by ocean thermal energy, can reduce electrical energy consumption. Simulations of SMC (sliding mode control) and conventional PID control were conducted, and the results showed that the SMC method has advantages in terms of response speed, overshoot, and energy saving. A lake test was conducted and the results showed that the new control method can make the equipment reach the fixed water depth position; however, due to the complex water flow environment, the precision and stability of the controller need to be improved in the future.

Study on the Optimal Design for Cavitation Reduction in the Vortex Suction Cup for Underwater Climbing Robot - Yibing Zhao; Canjun Yang; Yanhu Chen; Jia Li; Siyue Liu; Guoyun Ye (Journal of Marine Science and Engineering, 2022)
In order to adhere to the wall stably in an underwater environment, a vortex suction cup that injects high-pressure water inside via two axisymmetrically side-distributed inlets to create a negative pressure area in the center is the necessary component for the underwater climbing robot (UCR). However, the suction force of this vortex suction cup is reduced and periodically unstable due to unstable cavitation. The aim of this paper is to propose a cavitation reduction optimization method for vortex suction cups and to verify the effectiveness of the optimization. Analyses of this vortex flow, including streamlines, pressure, and cavitation number fluctuations, were carried out by the introduced computational fluid dynamics (CFD) simulating methods based on the multiphase RNG k−ε model to study the periodic fluctuations of the suction force of the original suction cup and the optimized ones. Force measurement and vortex observation experiments were conducted to compare the suction force of the original vortex suction cup and the optimized suction cup, as well as the cavitation and pressure fluctuation phenomenon. Results of simulation and experiments prove the existence of the effect of vortex cavitation on the suction performance and verify the rationality of optimization as well.

Buoyancy Regulation Strategy for Underwater Profiler Based on Adaptive Genetic Algorithm - Hui Zhi; Puzhe Zhou; Yanhu Chen; Xiaoyan Zhao; Yuandong Hong; Mingwei Lin; Canjun Yang (Journal of Marine Science and Engineering, 2021)
Considering the energy limitations of underwater vehicles, a strategy for energy saving is proposed. In the proposed buoyancy regulation strategy, oil of the buoyancy regulation system is pumped out several times at different depths instead of all at once. A balance between energy and time is achieved by assigning suitable weights, and the optimised depth which can be obtained from the pressure sensor is used as the judgement threshold based on the adaptive genetic algorithm. Through the numerical simulation using sea trial data, the influence of weight selection on energy and time is explored, and the frequency of oil draining for the vehicle to ascend is optimised. Simulation results show that the proposed buoyancy regulation strategy can save energy effectively when the frequency of oil draining is 4 times within depths of 0–500 m. Finally, trials were performed in Qiandao Lake and verify the contradictory relationship between energy and time.

The pressure compensation technology of deep-sea sampling based on the real gas state equation - Shuo Wang; Shijun Wu; Canjun Yang (Acta Oceanologica Sinica, 2020)

Seasonal and sexual variation in vigilance behavior of goitered gazelle (Gazella subgutturosa) in western China - Canjun Xia; Wenxuan Xu; Weikang Yang; David Blank; Jianfang Qiao; Wei Liu (Journal of Ethology, 2011)